Development of Conceptual Framework to Bridge the Gap in Higher Education Institutions towards Achieving Sustainable Development Goals (SDGs) - Kumaran Lechimi Kanthan; Khar Thoe Ng (UM Purwokerto Press, 2023)
This article reports part of a bigger scale study aiming at investigating the current gap in Higher Education Institutions (HEIs) through whole institutional approach integrating sustainable development application and the relationship to achieving aim of Education for Sustainable Development (ESD) in Malaysia. The study that involves mixed-research method is intended to improve the role of HEIs as a vehicle towards Sustainable Development Goals (SDGs) of the nation by 2050 according to 12th Malaysian Plan. In this preliminary stage, only qualitative case study will be reported on how a conceptual framework is developed to bridge the gap of ‘Education and Business’ (abbreviated as E-B) with focus on the need to cultivate the practice of SDG in all disciplines including institutional management of HEIs. In the advent of digital era, globalization and digitalization are connecting the world. It is expected that the development of conceptual framework will serve as planning guide for the proponent or researcher of this study, university administrators and sustainability practitioners who are expected to explore appropriate ways to integrate sustainability into institutional missions, strategies, curriculum and daily operations